2018
DOI: 10.1038/s41418-018-0213-5
|View full text |Cite
|
Sign up to set email alerts
|

Consensus report of the 8 and 9th Weinman Symposia on Gene x Environment Interaction in carcinogenesis: novel opportunities for precision medicine

Abstract: The relative contribution of intrinsic genetic factors and extrinsic environmental ones to cancer aetiology and natural history is a lengthy and debated issue. Gene-environment interactions (G x E) arise when the combined presence of both a germline genetic variant and a known environmental factor modulates the risk of disease more than either one alone. A panel of experts discussed our current understanding of cancer aetiology, known examples of G × E interactions in cancer, and the expanded concept of G × E … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 213 publications
0
19
0
Order By: Relevance
“…Various studies identified genetic factors that confer susceptibility to MM, highlighting the need for genetic testing in some patients and their relatives, which could result in earlier diagnosis or provide the opportunity for possible selective treatments. It is estimated that at least 12% of MMs develop in carriers of genetic mutations: beyond BAP1 , which is found inactivated by both germline and somatic mutations in MM, other tumor suppressor genes, such as TP53 and BRCA2 , or genes that regulate DNA repair, bear germline mutations in MMs 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Various studies identified genetic factors that confer susceptibility to MM, highlighting the need for genetic testing in some patients and their relatives, which could result in earlier diagnosis or provide the opportunity for possible selective treatments. It is estimated that at least 12% of MMs develop in carriers of genetic mutations: beyond BAP1 , which is found inactivated by both germline and somatic mutations in MM, other tumor suppressor genes, such as TP53 and BRCA2 , or genes that regulate DNA repair, bear germline mutations in MMs 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to “spontaneous” and “induced” somatic mutations, a growing percentage of cancers are attributed to inherited mutations of DNA repair genes and of other genes that, when mutated, accelerate the accumulation of DNA damage and/or the percentage of cells carrying DNA damage . Inherited mutations may also increase susceptibility to environmental carcinogens (GxE interaction) .…”
Section: Carcinogenic Mechanismsmentioning
confidence: 99%
“…In addition to “spontaneous” and “induced” somatic mutations, a growing percentage of cancers are attributed to inherited mutations of DNA repair genes and of other genes that, when mutated, accelerate the accumulation of DNA damage and/or the percentage of cells carrying DNA damage . Inherited mutations may also increase susceptibility to environmental carcinogens (GxE interaction) . Thus, the previous hypothesis, which focused almost exclusively on identifying human carcinogens to understand why cancer developed in some individuals, is now being integrated with studies aimed at including GxE interactions, which may better account for the observation that many are exposed but only few get cancer and that some cancers occur in unexposed individuals …”
Section: Carcinogenic Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of factors, such as environmental or occupational exposure to tobacco and biological infection by Schistosoma haematobium, were proved to be associated with the onset of bladder cancer [4,5]. Some hereditary genetic alterations that are involved in carcinogen bioactivation and detoxification may possibly make an individual more susceptible to extrinsic carcinogens [6,7]. Moreover, the accumulation of genetic changes and epigenetic alterations may contribute to the initiation and progression of human cancers, including bladder cancer [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%